The high-Z hydrogen-like atom: a model for polarized structure functions - Artru, X.; Benhizia, K. (Вопросы атомной науки и техники, 2007)
The Dirac equation offers a precise analytical description of relativistic two-particle bound states, when one of the constituent is very heavy and radiative corrections are neglected. Looking at the high-Z hydrogen-like atom in the infinite momentum frame and treating the electron as a "parton", various properties usually attributed to the quark distributions in the nucleon are tested, in particular: Bjørken scaling; charge, helicity, transversity and momentum sum rules; existence of the parton sea; Soffer inequality; correlation between spin and transverse momentum (Sivers and Boer-Mulders effects); transverse displacement of the center-of-charge and its connection with the magnetic moment. Deep inelastic experiments with photon or positron beams at MeV energies, analogous to DIS or Drell-Yan reactions, are considered. Рівняння Дірака дає точний аналітичний опис релятивістських зв'язаних станів із двома частинками, якщо одна з них дуже важка, а радіаційними поправками можливо знехтувати. Розглядаючи воднеподібний атом з великим Z у системі нескінченного імпульсу та трактуючи електрон як "партон", перевірено різні властивості, звичайно приписувані розподілам кварків у нуклоні, зокрема: Б’йоркенівський скейлінг; правила сум для заряду, спіральності, поперечної поляризації, імпульсу; існування партонів “моря”; нерівність Соффера; кореляція між спином і поперечним імпульсом (ефекти Сіверса та Бура-Малдерса); поперечне зміщення центру заряду та його зв'язок з магнітним моментом. Розглянуто експерименти з глибоконепружного розсіювання фотонних або позитронних пучків мегаелектронвольтних енергій, подібні до глибоконепружного розсіяння або процесу Дрела-Яна. Уравнение Дирака дает точное аналитическое описание релятивистских связанных состояний двух частиц, если одна из них очень тяжелая, а радиационными поправками можно пренебречь. Рассматривая водородоподобный атом с большим Z в системе бесконечного импульса и трактуя электрон как "партон", проверены различные свойства, обычно приписываемые распределениям кварков в нуклоне, в частности, Бьёркеновский скейлинг; правила сумм для заряда, спиральности, поперечной поляризации, импульса; существование “моря” партонов; неравенство Соффера; корреляция между спином и поперечным импульсом (эффекты Сиверса и Бура-Малдерса); поперечное смещение центра заряда и его связь с магнитным моментом. Рассмотрены эксперименты по глубоконеупругим процессам на фотонных или позитронных пучках мегаэлектронвольтных энергий, аналогичные глубоко неупругому рассеянию, либо процессу Дрелла-Яна.